Level of M1 GABAB predicts micro offline consolidation of motor learning during wakefulness - Pasquale Cardellicchio; Sara Borgomaneri (npj Science of Learning)
Abstract The consolidation process stabilizes a new initially labile memory. This consolidation could operate on a shorter timescale during wakefulness after initial motor learning. Within micro-offline learning states, sequences of simple individual actions learned through interleaved practice are condensed into a unified skill through a time-dependent consolidation process occurring during wakeful periods. While emerging evidence links Glutamate and GABA modulations in the primary motor cortex (M1) to motor learning, its relationship with micro-offline consolidation processes in brief resting states during motor learning is unclear. To investigate this issue, we employed Transcranial magnetic stimulation (TMS) to evaluate whether interindividual variation of different neurotransmitters at rest influences motor learning consolidation in humans. Our results point to the role of GABAB in micro-offline motor consolidation processes during motor learning in M1. This finding could have an important impact on planning neuropharmacology or non-invasive brain stimulation approaches in clinical domains, such as post-stroke rehabilitation.